Revisitando a temática sobre avaliação: uma revisão das dissertações do Programa de Pós-Graduação em Educação: Formação de Formadores (Formep) - Bassani, Cristiane (2024)
Educational assessment is often relegated to the background in teaching practice, often being reduced to numerical scales that attempt to quantify an alleged appropriation of content based on imprecise instruments and scales. Along these lines, the emergence of professional master's degrees in the pedagogical area has proven to be a fruitful space for discussing this topic, with the implementation of educational products that seek reflection on assessment methods. Therefore, the present dissertation aims to carry out an investigation into the theme of Assessment defended in the Postgraduate Program in Education Training of Trainers (Formep-PUCSP), in the period from 2015 to 2022. To this end, the methodology employed consisted of reviewing systematic approach to such work. The results indicated 57 dissertations that focused on Educational Assessment as the main topic. Of these, 24 referred to the dimension of Learning Assessment, delving into 3 categories: concepts and practices (12 works), assessment instruments (6 works) and training of education professionals (6 works). This academic cut allowed us to infer the prevalence of researches applied in the public education network, with a balance between teaching stages and focused on processes involving the teachers. The conclusions highlight the importance of the context of the professional master's degree, particularly in the line of research on Educational Assessment, so that the demands of the school enter the university. Thus, it is suggested that there is a need for further research on Assessment at all educational stages, seeking to transform negative memories and experiences of teachers in relation to assessment processes, in addition to their unequivocal inherence with teaching-learning processes